Behavior recognition for humanoid robots using long short-term memory - How D.N.T.; Loo C.K.; Sahari K.S.M. (SAGE Publications Inc., 2023)
Anthropomorphic robots; Brain; Complex networks; Demonstrations; Neural networks; Recurrent neural networks; Robots; Teaching; Behavior recognition; Building blockes; Deep learning; Learning from demonstration; Long short term memory; LSTM; Network frameworks; Simple behaviors; Behavioral research